History of Iban popular music, an alternative conceptions of modernity - Lim, Connie Keh Nie; Durin, A.; Chelum, A.; Magiman, Mohamad Maulana (2016)
The Iban make up one third of the Sarawakian population and are the largest indigenous ethnic group in Sarawak, Malaysia. As with other ethnicities in the nationstate, modernity has presented challenges for socio-cultural development and lifestyle of Iban people. The objective of this paper is to examine how modernity has historically shaped developments in the industry of Iban popular music. Historically, the Iban are a cultural group located geographically and politically on the periphery of the multi-cultural nation of Malaysia. Throughout much of the 20th century, the music industry has experienced a rapid embrace of modernity through the nation to the detriment of traditional practices in culture in order to adapt them in the era of modernization. Hence, the Iban society had gone through a state of flux where people have gone through the process of readapting themselves in meeting the demanding challenges of Malaysian nationalism. Drawing upon alternative conceptions of modernity to evaluate how the Iban reference both a national as well as a local music industry particularly through their use of language as an expression of Iban. Changes in Iban society through political and economic modernization had led to the emergence of Iban popular music industry because of relative exposure to agents of change such as the influence through Christian missionary and education. This reflects how the Iban react and reflect in adaptation of modern demands of change as a result of the effects of historical processes on the social, cultural and physical environments.